IMPLEMENTASI SERTIFIKASI FSC (FOREST STEWARSHIP COUNCIL) TERHADAP ECO-PRODUCT DI INDONESIA - Retno Dwi Palupi; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is trying to explain about Implementation of FSC (Forest Stewarship Council) Certification on Eco-Products in Indonesia. FSC (Forest Stewarship Council) is an international organization non-profit, independent, non-goverment to promote responsible forest management in the world.This research is using perspective Pluralism, theory green thought and international organization, and level of analysis is non-governmental organization. This research is also applying qualitative methods and the data obtained comes from book, journals, documents, articles, interest sites and other sources telated to this research.Implementation of FSC sertification for eco-product that is to consumer goods in Indonesia. Eco-product are environmental friendly products. The purchasing power of Indonesia society in general is still relatively low in the appeal of Europe. Currently FSC Indonesia purpose to improved public awareness about the benefits of FSC labels. In Indonesia eco-product that use FSC label are products that are produced by FSC partners that is Tetra Pak, SIG Combibloc, Faber Castell, Tissue Tessa, and IKEA.Keywords: FSC (Forest Stewarship Council), Eco-Product, Consumer Goods, Enviromental Friendly